Improving Students Ability in Writing Hortatory Exposition Texts by Using Process-Genre Based Approach with YouTube Videos as the Media - fifin naili rizkiyah (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2017)
This research is aimed at finding out how Process-Genre Based Approach strategy with YouTube Videos as the media are employed to improve the students’ ability in writing hortatory exposition texts. This study uses collaborative classroom action research design following the procedures namely planning, implementing, observing, and reflecting. The procedures of carrying out the strategy are: (1) relating several issues/ cases to the students’ background knowledge and introducing the generic structures and linguistic features of hortatory exposition text as the BKoF stage, (2) analyzing the generic structure and the language features used in the text and getting model on how to write a hortatory exposition text by using the YouTube Video as the MoT stage, (3) writing a hortatory exposition text collaboratively in a small group and in pairs through process writing as the JCoT stage, and (4) writing a hortatory exposition text individually as the ICoT stage. The result shows that the use of Process-Genre Based Approach and YouTube Videos can improve the students’ ability in writing hortatory exposition texts. The percentage of the students achieving the score above the minimum passing grade (70) had improved from only 15.8% (3 out of 19 students) in the preliminary study to 100% (22 students) in the Cycle 1. Besides, the score of each aspect; content, organization, vocabulary, grammar, and mechanics also improved